2020
DOI: 10.1108/bij-10-2019-0439
|View full text |Cite
|
Sign up to set email alerts
|

The effect of investment in green technology in a two echelon supply chain under strict carbon-cap policy

Abstract: PurposeStrict carbon-cap policy is one of the basic policies proposed by the regulatory bodies to reduce the anthropogenic greenhouse gas emission. The purpose of this paper is to examine whether it is beneficial for a company to invest in green technology or not under the strict carbon-cap policy and for that a two echelon supply chain model is developed. This paper gives insight about judicious decision about investment on green te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…In addition, investments in green technologies can lead to a reduction in the total cost of the supply chain, as well as to a reduction in carbon emissions, [24]. Following the analysis of the data obtained from 16,119 companies, the results showed that there is a positive relationship between corporate social responsibility (CSR) and the financial performance of companies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, investments in green technologies can lead to a reduction in the total cost of the supply chain, as well as to a reduction in carbon emissions, [24]. Following the analysis of the data obtained from 16,119 companies, the results showed that there is a positive relationship between corporate social responsibility (CSR) and the financial performance of companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a strong relationship between financial returns and sustainability, explained by the level of performance for all the metrics analyzed (Carhart's alpha, Sharpe, net return, reduced cost). Ghosh, Sarmah, and Kanauzia (2020) [24]; Li et al (2020) [82] Duran-Santomil et al (2019) [92]; Kim and Lee (2018) [86]; Ganda and Milondzo (2018) [23]; Teti et al (2015) [70]; Yadav, Han, and Rho (2015) [69] With responsible management and strategy, the firms can use tools to optimize their performance, improving sustainability while not necessarily sacrificing financial outcomes and making the company more profitable and more likely to survive in the long run.…”
Section: Financial Performancementioning
confidence: 99%
“…Mohammed et al (2017) optimized the design and planning of a multi-period close-loop supply chain under different carbon policies (including strict carbon cap policy) with demand and return uncertainties. Ghosh et al (2020b) examined the effect on green investment in a two-echelon supply chain with random demand under strict carbon cap policy. All the papers I have discussed here optimized production–inventory or supply chain models under strict carbon cap policy, but none of them considered defective items.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To illustrate my proposed model and to get outcomes (for the base case and sensitivity analyses) the following data set is considered. Most of the data are taken from published papers like – Ouyang et al (2004), Ghosh et al (2017), Ghosh et al (2020b)…”
Section: Solution Procedure Numerical Values For Parameters and Base ...mentioning
confidence: 99%
See 1 more Smart Citation